2020
DOI: 10.1038/s41390-020-0975-6
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete resection of necrotic bowel may increase mortality in infants with necrotizing enterocolitis

Abstract: Background: Infants with advanced NEC often need surgical resection of necrotic bowel. We hypothesized that incomplete resection of NEC lesions, signified by the detection of necrotic patches in margins of resected bowel loops, results in inferior clinical outcomes. Methods: We reviewed the medical records of infants with surgical NEC in the past 15 years for demographic, clinical, and histopathological data. We also developed statistical models to predict mortality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…All showed findings of NEC, including necrosis, inflammation, and hemorrhages, and some showed regenerative changes. Consistent with our earlier observations, 17 necrosis, inflammatory changes, and hemorrhages correlated with each other. Pneumatosis was seen in about 30% of the sections.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…All showed findings of NEC, including necrosis, inflammation, and hemorrhages, and some showed regenerative changes. Consistent with our earlier observations, 17 necrosis, inflammatory changes, and hemorrhages correlated with each other. Pneumatosis was seen in about 30% of the sections.…”
Section: Discussionsupporting
confidence: 92%
“…We have recently shown that incomplete resections of necrotic bowel may increase mortality in NEC. 17 There may be some justification for on-site, rapid histopathological screening of the resected tissues to prevent excessive removal of segments that could possibly recover in time, but also to ensure that all clearly necrotic patches have been removed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that incomplete resection of inflamed intestine was associated with longer hospital stay and mortality than complete resection. 31 The reasons and mechanisms leading to greater severity of BPD in pre-term infants are still not fully understood. Toll-like receptor 4 activation by LPS has been associated with NEC in animal model studies.…”
Section: Discussionmentioning
confidence: 99%